PHYTOCHEMICAL SCREENING AND ANALGESIC, ANTI-BACTERIAL AND CYTOTOXIC ACTIVITY EVALUATION OF ETHANOL EXTRACT OF PITHCELLOBIUM DULCE ( ROXB.) BENTH LEAF - Ur Rashid, MOHAMMED HARUN; Biswas, Sujit; MOHAMMED ABDULLAH-AL-MAMUN,; Huque, Amdadul; Bhuiyan, Jamilur Rahman (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Introduction: Pithcellobium dulce (Roxb.) benth, tree 5-18 m high, with pendulous branches, short, sharp stipular spines. It belongs to Fabaceae family. This plant's accession number is 31,388 as per Bangladesh national herbarium. Methods: For the investigation of its phytochemical and biological activities, the concentrated ethanolic extract of the leaf were extracted. Objective: This crude extract was tested for the presence of various chemical groups and alkaloid, flavonoids, saponin and reducing sugar were identified. The traditional medicinal use of this plant prompted us to check analgesic, anti-bacterial, anti-diarrheal and cytotoxic effects. Result and Discussion: The ethanol extract of the leaf produced 29.4% and 61.54% protection or writhing inhibition in mice at orally dosage of 250 mg/kg (p<0.001) and 500 mg/kg (p<0.001) body weight of mice, respectively. This was comparable to the standard drug diclofenac sodium at the dose of 25 mg/kg of body weight. This extract increased mean latent period and decreased the frequency of defecation significantly at the oral dose of 500 mg/kg body weight, which is also comparable to standard loperamide at dose of 50 mg/kg body weight. This leaf extract also showed antimicrobial activity only against shigella dyst-1 among 10 bacterial species culture. In addition, it also showed cytotoxic effect-50% (LC50) mortality of Brine Shrimp nauplii occurred at 20 Î¼g/ml and 90% (LC90) mortality at 80 Î¼g/ml ethanolic leaves crude extract. Conclusion: Most of the medicinal plants of Bangladesh have more or less biological activity. It was a preliminary study; further study can be done for the fulfillment of this experiment based on different extract concentration. Keywords: Reagent, Dulce, Extract, Benth Leaf.